1988
DOI: 10.1128/aac.32.8.1257
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of a new type of UDP-glucose analog against herpesvirus replication

Abstract: The mode of action of a new type of UDP-glucose analog against herpes simplex virus type 1 (HSV-1) replication was examined. The analog showed good selectivity and potent activity. At 10 ,ug/ml, P-536 inhibited the formation of infectious HSV-1 by more than 90%, whereas at 100 ,ug/ml it had no cytotoxic effects, as evidenced by phase-contrast microscopy. P-536 showed a wide spectrum of action and was active against HSV-1, adenovirus type 5, vaccinia virus, poliovirus type 1, encephalomyocarditis virus, vesicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…One hour later, the medium was removed, and the proteins were collected for electrophoresis in 15% polyacrylamide gels as previously described (1,5). To obtain specific * Corresponding author.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One hour later, the medium was removed, and the proteins were collected for electrophoresis in 15% polyacrylamide gels as previously described (1,5). To obtain specific * Corresponding author.…”
mentioning
confidence: 99%
“…To assay for protein synthesis cells were incubated in methionine-free medium in the presence of 5 ,uCi of [35S]methionine (1,100 Ci/mmol; The Radiochemical Centre) per ml. One hour later, the medium was removed, and the proteins were collected for electrophoresis in 15% polyacrylamide gels as previously described (1,5).…”
mentioning
confidence: 99%
“…[1] Furthermore, studies of structurally related compounds within this series showed that the nucleotide-like 5'-Osulfamoyluridine moiety is an important component for the maintenance of antiviral activity, and it was suggested that this moiety and/or its metabolites could be responsible for the observed inhibition of DNA synthesis and protein glycosylation. [2] More recently, lipophilic nucleotide mimics in which 2',3'-dideoxynucleoside (ddN) residues were linked to a glucopyranosyl moiety by the OSO 2 NHCOO group were shown to exhibit anti-HIV-1 activity in MT-4 cells at concentrations well below the toxicity threshold. [3] In this case, it was suggested that these compounds do not release the free ddNs, which are known to be potent and selective inhibitors of HIV replication (by inhibiting HIV reverse transcriptase), but may act in their own right.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic materials DNA and RNA are phosphodiesters, and most of the coenzymes are esters of phosphoric or pyrophosphoric acid. Recently, a new type of analogue of uridine 5‘-diphosphate glucose (UDP-Glc), in which the naturally occurring diphosphate group has been replaced by an isosteric O−SO 2 NHCO−O group, were found to interfere with protein glycosylation, inhibiting the glycosylation of viral proteins to a greater extent than glycosylation of cellular proteins . Although these analogues were initially designed to interfere with the glycosylation process and, do in fact, inhibit it, their mode of action proved to be more complex since they also inhibit DNA synthesis 1b.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new type of analogue of uridine 5‘-diphosphate glucose (UDP-Glc), in which the naturally occurring diphosphate group has been replaced by an isosteric O−SO 2 NHCO−O group, were found to interfere with protein glycosylation, inhibiting the glycosylation of viral proteins to a greater extent than glycosylation of cellular proteins . Although these analogues were initially designed to interfere with the glycosylation process and, do in fact, inhibit it, their mode of action proved to be more complex since they also inhibit DNA synthesis 1b. In recent therapeutic strategies, the extended use of the −SO 2 NHCO− groupas a replacement for the diphosphate or sulfate moiety of a variety of critical biomoleculesproved to be successful as well. Also, the ionized form of this spacer was used to design an unusual water-soluble ACAT inhibitor which is well absorbed and thus exhibits improved bioavailability …”
Section: Introductionmentioning
confidence: 99%